Multi-Fact Correction in Abstractive Text Summarization - Dong, Yue; Wang, Shuohang; Gan, Zhe; Cheng, Yu; Cheung, Jackie Chi Kit; Liu, JJ (Jingjing) (The 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP 2020), 2020)
Pre-trained neural abstractive summarization systems have dominated extractive strategies on news summarization performance, at least in terms of ROUGE. However, system-generated abstractive summaries often face the pitfall of factual inconsistency: generating incorrect facts with respect to the source text. To address this challenge, we propose SpanFact, a suite of two factual correction models that leverages knowledge learned from question answering models to make corrections in system-generated summaries via span selection. Our models employ single or multi-masking strategies to either iteratively or autoregressively replace entities in order to ensure semantic consistency w.r.t. the source text, while retaining the syntactic structure of summaries generated by abstractive summarization models. Experiments show that our models significantly boost the factual consistency of system-generated summaries without sacrificing summary quality in terms of both automatic metrics and human evaluation.